2020
DOI: 10.37496/rbz4920190096
|View full text |Cite
|
Sign up to set email alerts
|

Effect of fermented soybean meal supplementation on some growth performance, blood chemical parameters, and fecal microflora of finishing pigs

Abstract: This study evaluated the effect of fermented soybean meal (FSBM) supplementation on growth performance, meat quality, blood biochemical parameters, and fecal microflora of finishing pigs. Thirty-two crossbred pigs (Duroc × Landrance × Yorkshire) (66-day-old, 67.95±0.25 kg) were randomly allocated to two treatments and fed diets containing soybean meal and FSBM. The average daily gain (ADG), average daily feed intake (ADFI), feed conversion ratio (FCR), blood biochemical parameters, and meat quality index were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 39 publications
(38 reference statements)
1
6
0
Order By: Relevance
“…Alpha diversity can be utilized as an indicator of the functional resilience of ecological diversity of the intestinal microbiota, including species richness indices (Observed species, Chao, and Ace), and species diversity (Shannon and Simpson) 46 . In the current study, dietary inclusion with FSBM significantly increased the Shannon, Simpson, and Chao1 richness, which was in accordance with our previous findings in pigs that dietary inclusion of FSBM significant difference the Shannon, Simpson 47 . Bacteroidetes, Firmicutes, Actinobacteria, Proteobacteria, and Tenericutes were the most pre-dominant bacteria phylum in the piglets 48 .…”
Section: Discussionsupporting
confidence: 93%
“…Alpha diversity can be utilized as an indicator of the functional resilience of ecological diversity of the intestinal microbiota, including species richness indices (Observed species, Chao, and Ace), and species diversity (Shannon and Simpson) 46 . In the current study, dietary inclusion with FSBM significantly increased the Shannon, Simpson, and Chao1 richness, which was in accordance with our previous findings in pigs that dietary inclusion of FSBM significant difference the Shannon, Simpson 47 . Bacteroidetes, Firmicutes, Actinobacteria, Proteobacteria, and Tenericutes were the most pre-dominant bacteria phylum in the piglets 48 .…”
Section: Discussionsupporting
confidence: 93%
“…Moreover, fermentation with B. subtilis can improve the taste of feed, secrete digestive enzymes, stimulate digestion and absorption of nutrients (60), and produce bacitracin, polymyxin, nystatin, and gramicidin, which inhibit pathogen growth (61). Addition of FSBM to feed increased the activity of digestive enzymes (trypsin, lipase, and protease), improved the FCR and growth of weaned piglets (62), and increased the average daily gain (ADG) of finishing pigs (63). Similarly, using fermented feed, such as SBM, improved the morphological parameters of the intestine, increased nutrient absorption, and increased BWG in broilers (64).…”
Section: Figure 3 |mentioning
confidence: 99%
“…High levels of HDL were found in the serum of turkeys fed 7 or 9% FSBM (64). Moreover, pigs fed FSBM diets had significantly lower creatinine concentrations than those fed control diets (63). The reduction of cholesterol and TAG levels after feeding on FFB may be attributed to the role of probiotic produced during fermentation in inhibiting 3-hydroxy-3-methylglutaryl CoA reductase enzyme incorporated in cholesterol biosynthesis (84).…”
Section: Figure 3 |mentioning
confidence: 99%
“…Wu et al [42] reported evidence indicated a close relationship among Prevotella and long period of time carbohydrates diets or carbohydrates from ber-rich diets. Feng et al [43] and Forsyth et al [44] reported a higher Prevotella abundance, the higher the mucin composite content, but bacterial toxins would reduce gut penetrability and the sensitivity of the region-speci c gut to systemic exposure. Accordingly, higher in the Prevotella abundances in FSBM it could be helpful in improve on growth performance in weaning piglets.…”
Section: Discussionmentioning
confidence: 99%